Filtration Processes and Design of Filters - Miguel, António F. (2013)
The process of filtration is widely used from domestic use to industry. Filters are used in vacuum cleaners and air conditioning systems but also in a wide variety of critical applications such as in the nuclear, electronic, aerospace, pharmaceutical and medical fields. How filtration process takes place? What kinds of filters are available? How to design good filters? This chapter is devoted to filtration theory, design and international standards for efficient air filters. It represents an attempt to bridge a gap in the literature by presenting an integrated view of the current state of art in this fascinating field of filtration.